2022
DOI: 10.3390/sym14010081
|View full text |Cite
|
Sign up to set email alerts
|

CardioVR-ReTone—Robotic Exoskeleton for Upper Limb Rehabilitation following Open Heart Surgery: Design, Modelling, and Control

Abstract: Following cardiac surgery, patients experience difficulties with the rehabilitation process, often finding it difficult, and therefore lack the motivation for rehabilitation activities. As the number of people aged 65 and over will rise by 207 percent globally by 2050, the need for cardiac rehabilitation will significantly increase, as this is the main population to experience heart problems. To address this challenge, this paper proposes a new robotic exoskeleton concept with 12 DoFs (6 DoFs on each arm), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In this paper, we discussed the design and the preliminary implementation of a new home-based cardiac telerehabilitation system enhanced by a robotic and Virtual Reality (VR) systems—called RoboTeleRehab. This work was based on our earlier efforts highlighted within the references [ 1 , 2 ], and it represents the expansion of cardiac patients’ assisted rehabilitation from specialist facilities and hospitals to home-based centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we discussed the design and the preliminary implementation of a new home-based cardiac telerehabilitation system enhanced by a robotic and Virtual Reality (VR) systems—called RoboTeleRehab. This work was based on our earlier efforts highlighted within the references [ 1 , 2 ], and it represents the expansion of cardiac patients’ assisted rehabilitation from specialist facilities and hospitals to home-based centers.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with heart failure who participated in a 12-week tele-rehabilitation HBCR program showed no significant improvement in the 6-min walk distance from CBCR at the conclusion of the program [ 38 , 39 ]. Secondarily, findings on patient contentment, quality of life, and muscle strength likewise indicated that the two groups were equivalent [ 1 ]. Participants in the CopenHeartRFA study selected between HBCR and CBCR after either atrial fibrillation ablation or heart valve surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobots have been used before, but in industries related to manufacturing [8][9][10][11], medical sector [12][13][14][15] or even in domains such as cognitive architectures [16][17][18]. The problem of integrating cobots into the soldering process was not studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…This section presents the state of the art of rigid exoskeletons. CardioVR-ReTone [40] is a good example of this, which consists on two serial robotic arms, each with six Degrees Of Freedom (DOFs), and with mirrored joints (Fig. 2.9).…”
Section: Soft and Rigidmentioning
confidence: 99%